C5aR contributes to the weak Th1 profile induced by an outbreak strain of Mycobacterium tuberculosis - Sabio y García, Carmen Alejandra (2017)
Fil: Sabio Y García, Carmen Alejandra. Academia Nacional de Medicina. Instituto de Medicina Experimental; Argentina.